Teachers' Challenges in Promoting Learner Autonomy - Marzuki, Marzuki; Indrawati, Inda; H, Ismail Yunus (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2023)
The concept of learner autonomy has garnered significant attention from scholars, educators, policy makers, and researchers across various countries. However, In Indonesia, the body of research dedicated to learner autonomy is still growing, with specific attention needed to identify potential obstacles that might deter its promotion. This study, therefore, aims to delve into the socio-cultural challenges encountered by secondary school teachers when fostering learner autonomy.This investigation is crucial, as socio-cultural influences appear to be a significant barrier for English as a Foreign Language (EFL) students in Indonesia. The study adopted a qualitative descriptive research approach, utilizing a purposive sampling technique to select participants based on specific criteria. These included senior high school teachers with over five years of experience at their respective schools, who were also willing to participate in interviews. In total, six English teachers from different senior high schools within a single Indonesian province contributed to this study. The data were collected through semi-structured interviews, and the teachers' responses were quoted and interpreted in light of the data analysis and supporting theories from relevant literature. The findings revealed three primary socio-cultural barriers impeding the promotion of learner autonomy: (1) barriers due to language issues, (2) barriers related to a limited worldview, and (3) institutional barriers. This research implies that promoting learner autonomy in language learning requires adjustments in teaching strategies, curriculum design, and institutional policies. Research suggestions are also provided to further research to address the limitation of the current study.